Reduction in acute bee paralysis virus Infection and mortality in honey bees (Apis mellifera) by RNA interference technology - Ferrufino, Cecilia Gabriela (2025)
In Argentina, various studies have reported the detection of multiple viruses in honey-producing and queen-rearing apiaries, with Aparavirus apisacutum, the causal agent of acute bee paralysis (ABP), demonstrating a particularly high prevalence. The potential of RNA interference (RNAi) as a strategy to control honey bee viruses has been explored, with initial findings indicating that RNAi could aid in mitigating the economic losses associated with viral infections. This study aimed to evaluate the effect of RNAi technology mediated by double-stranded RNA (dsRNA) on the dynamics of ABPV infection in adult honey bees. Fragments of the ABPV replicase and VP1 genes were used as templates for dsRNA synthesis via in vitro transcription. A gene silencing experiment was conducted through oral administration using five treatments: control, specific dsRNA + Virus, Virus alone, specific dsRNA alone, and non-specific dsRNA + virus. Bee survival was recorded over 10 days for all treatments, and samples were subsequently processed for viral quantification using quantitative real-time PCR. The oral administration of specific dsRNA reduced the viral replication curve, decreased the average viral loads and increased bee survival. This is the first report demonstrating the reduction in ABPV infection in adult honey bees through post-transcriptional gene silencing achieved via oral administration of dsRNA.